Spinal ranges of motion in boys with pectus excavatum - Lizis, Paweł; Puszczałowska-Lizis, Ewa (Zamiejscowy Wydział Wychowania Fizycznego w Białej Podlaskiej, 2009)
Aim. The lack of comparative research into the spinal ranges of motion and somatic features of children with pectus excavatum and healthy children was the reason for taking up this topic. The aim of this work was to compare the spinal ranges of motion and basic somatic features of boys with pectus excavatum with healthy children. Material and methods. The study included 30 boys from Sucha Beskidzka commune. Fefteen subjects had pectus excavatum, whereas the remaining 15 boys were healthy and they constituted the control group. The mean age of the subjects was 13,3 ± 0,4 and 13,5 ± 0,7. The study was carried out in 2008. The spinal range of motion was measured with the use of the SFTR method. Also, body height, body mass as well as chest inspiratory and expiratory volume were measured. Results. Smaller ranges of motion of the spine were observed in boys with pectus excavatum. Significant differences concerned lateral flexions of thoracolumbar spine, the flexion of the lumbar spine, as well as the flexion of the whole spine. Significant differences between the groups were found in the chest circumference. Conclusions. Significant differences in some ranges of motion of the spine between the groups are caused by rachitis. Statistically significant differences in chest circumference indicate that rachitis exerts negative influence on the range of motion of the chest and on the respiratory system.
Keywords: boys; spine; range of motion; somatic features